(untitled) (Research, Society and Development, 2022)
Cholecystectomy stands out as the most prevalent procedure in elective gastrointestinal surgeries, with more than sixty thousand annual hospitalizations in Brazil, which corresponds to one of the biggest public health problems. The aim of this study was to evaluate the epidemiological profile of patients submitted to cholecystectomy in a private hospital in southwestern of Goiás, with emphasis on modifiable risk factors. We analyzed 489 medical records of the surgeries performed from January 2016 to December 2020, of which 462 were included as a sample. The most common profile was characterized by: female gender, mean of 41 years, previous history of pregnancy and obesity. Identified 144 etilist patients, 78 smokers and 240 (51.56%) with associated comorbidities. 365 (79%) underwent laparoscopy surgery. The conversion rate was 1.08%. 95 (20.56%) patients presented surgical complications with statistical relationship to age, hypertension and dyslipidemia. It is concluded that the profile most susceptible to bile duct diseases should be the target of multiprofessional clinical conduct for early identification and treatment, with consequently reduction of surgical complications in the population.